2017
DOI: 10.5114/wiitm.2017.66515
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative hemoglobin drop after laparoscopic myomectomy.

Abstract: IntroductionLaparoscopic myomectomy (LM) can be associated with significant bleeding.AimTo identify factors influencing the postoperative hemoglobin (Hb) drop after LM.Material and methodsThis is a retrospective, single-center study. We evaluated data of 150 consecutive patients undergoing LM due to intramural myomas between 2010 and 2015.ResultsThe median age of the patients was 37 (23–53) years. The mean diameter of the largest myoma was 5.7 ±2.3 (1.5–12) cm. The mean surgical time was 83 ±38 (35–299) min. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(42 reference statements)
0
6
2
Order By: Relevance
“…The blood loss is related with different factors such as myomas' size and number. The localization in this work [35] has not found impact on the amount of blood lost, but in an another study, intramural myomas with a size between 8 and 12 cm had a higher amount of blood loss compared to sub-serosal myomas of the same size (median blood loss = 275 vs. 200, P < 0.05) [36].…”
Section: F O R P U B L I C a T I O Ncontrasting
confidence: 55%
See 1 more Smart Citation
“…The blood loss is related with different factors such as myomas' size and number. The localization in this work [35] has not found impact on the amount of blood lost, but in an another study, intramural myomas with a size between 8 and 12 cm had a higher amount of blood loss compared to sub-serosal myomas of the same size (median blood loss = 275 vs. 200, P < 0.05) [36].…”
Section: F O R P U B L I C a T I O Ncontrasting
confidence: 55%
“…In addition, the impact of the number of myomas was also evaluated ≥5 myomas were found to be significantly associated with blood transfusion requirements within 1 week of the myomectomy, and there was a linear increase in blood loss with the size of myoma [38]. Hemoglobin drop of more than 2 units g/dl was found when there were ≥3 myomas [39].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…The most seen complication was hemorrhage, and mean hemoglobin drop was 1.5 g/dl [8]. In a study about predictors of hemorrhage in laparoscopic myomectomy; the hemorrhage risk was found associated with the duration of surgery, the largest diameter of fibroid, the cumulative fibroid weight, and the number of the suture [9]. There are numerous studies about the prediction of hemorrhage risk in laparoscopic myomectomy, but none of them mention whether the location of fibroid is associated with the risk of hemorrhage or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…[8] In a study about predictors of hemorrhage in laparoscopic myomectomy, there was found that hemorrhage risk is associated with duration of surgery, largest diameter of fibroid, cumulative fibroid weight, and number of suture. [9] There are numerous studies about prediction of hemorrhage risk in laparoscopic myomectomy but none of them mention whether the location of fibroid is associated with the risk of hemorrhage or other complications. Based on these concerns, in our study we planned to detect whether hemorrhage and complication rates vary according the location of the dominant fibroid.…”
Section: Discussionmentioning
confidence: 99%